2018
DOI: 10.18843/ijms/v5i3(1)/05
|View full text |Cite
|
Sign up to set email alerts
|

Role of Strategic Human Resource Practices in Employee Performance

Abstract: HRM practices and policies, and their implementation in the business

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…By enabling workers to develop, learn, and progress in their careers, organizations that support career development programs lessen employee dissatisfaction and feelings of alienation from their jobs (Dawood, Shaalan, & Nsaif, 2022). A sense of purpose, direction, and advancement is fostered by offering employees chances for skill development, mentorship support (Goyal, Nigam, & Goyal, 2023), and career advancement (Koyuncu & DEMİRHAN, 2021). This can reduce job alienation and increase employee engagement and satisfaction (Odei-Tettey, 2021).…”
Section: Career Development Opportunitiesmentioning
confidence: 99%
“…By enabling workers to develop, learn, and progress in their careers, organizations that support career development programs lessen employee dissatisfaction and feelings of alienation from their jobs (Dawood, Shaalan, & Nsaif, 2022). A sense of purpose, direction, and advancement is fostered by offering employees chances for skill development, mentorship support (Goyal, Nigam, & Goyal, 2023), and career advancement (Koyuncu & DEMİRHAN, 2021). This can reduce job alienation and increase employee engagement and satisfaction (Odei-Tettey, 2021).…”
Section: Career Development Opportunitiesmentioning
confidence: 99%
“…Engagement is more strategic than others in terms of both employees and organizational outcomes [ 14 ]. Even if research on employee engagement has demonstrated that HPWSs are positively related to employee engagement [ 13 , 94 , 95 ], it is also not clear what HPWSs are most important for employee engagement and what theoretical mechanisms intervene in explaining the link between HPWSs and employee engagement [ 13 ]. Hence, more explanation about the relationship between HPWSs and engagement, particularly focusing on mediation, is needed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Human resource management (HRM) covers a variety of interrelated activities involving hiring, training, providing career development opportunities, and retaining personnel, which should be clear, precise, and goal‐driven to foster and enhance human talent (Johari et al., 2012). Past studies have firmly established the connection between HRM and employee engagement, supported empirically by social exchange theory which states that when organizations that offer HRM practices such as organizational support, thorough selection processes, competitive salaries, and continuous development opportunities are reciprocated with increased engagement by employees (Aktar & Pangil, 2018; Goyal et al., 2023; Marescaux et al., 2013; Saks, 2022). Pass and Ridgway (2022) proposed that increased autonomy allows individuals to be accountable for their engagement.…”
Section: Introductionmentioning
confidence: 99%